OsCERK1 and OsRLCK176 play important roles in peptidoglycan and chitin signaling in rice innate immunity. (December 2014) - Ao, Ying; Li, Zhangqun; Feng, Dongru; Xiong, Feng; Liu, Jun; Li, Jian‐Feng; Wang, Menglong; Wang, Jinfa; Liu, Bing; Wang, Hong‐Bin
Summary Microbe‐associated molecular pattern (MAMP)‐triggered immunity plays critical roles in the basal resistance defense response in plants. Chitin and peptidoglycan (PGN) are major molecular patterns for fungi and bacteria, respectively. Two rice (Oryza sativa) lysin motif‐containing proteins, OsLYP4 and OsLYP6, function as receptors that sense bacterial PGN and fungal chitin. These membrane receptors, which lack intracellular kinase domains, likely contain another component for transmembrane immune signal transduction. Here, we demonstrate that the rice LysM receptor‐like kinase OsCERK1, a key component of the chitin elicitor signaling pathway, also plays an important role in PGN‐triggered immunity in rice. Silencing of OsCERK1 suppressed PGN‐induced (and chitin‐induced) immunity responses, including reactive oxygen species generation, defense gene expression, and callose deposition, indicating that OsCERK1 is essential for both PGN and chitin signaling initiated by OsLYP4 and OsLYP6. OsLYP4 associated with OsLYP6 and the rice chitin receptor chitin oligosaccharide elicitor‐binding protein (CEBiP) in the absence of PGN or chitin, and treatment with PGN or chitin led to their disassociation in vivo. OsCERK1 associated with OsLYP4 or OsLYP6 when induced by PGN but it associated with OsLYP4, OsLYP6, or CEBiP under chitin treatment, suggesting the presence of different patterns of ligand‐induced heterooligomeric receptor complexes. Furthermore, the receptor‐like cytoplasmic kinase OsRLCK176 functions downstream of OsCERK1 in the PGN and chitin signaling pathways, suggesting that these MAMPs share overlapping intracellular signaling components. Therefore, OsCERK1 plays dual roles in PGN and chitin signaling in rice innate immunity and as an adaptor involved in signal transduction at the plasma membrane in conjunction with OsLYP4 and OsLYP6.